Evaluation of Hydraulic Performance of a Type of Vertical Axis Water Microturbine for Use in Medium Pressure Water Supply Network - Hossein Amjadi; Jaber Soltani; Morteza Khashehchi; Amirhosein Ahmadihaji (آب و فاضلاب, 2021)
One of the oldest methods of producing electrical energy is the use of latent energy in running water, which uses a water turbine to achieve this. It is one of the most important sources of renewable energy and has attracted the attention of many researchers in recent years. In this study, laboratory evaluation of hydraulic performance of a type of water microturbine to convert excess pressure in medium pressure water supply networks into electrical energy usable for sensors or equipment such as flow meters, pressure meters, leak detectors, etc., used to manage energy consumption and intelligent water supply networks is investigated. For this purpose, in three different scenarios, the effect of parameters such as flow rate, pressure and different angles of the guide vane on the microturbine performance and pressure drop was investigated. The results showed that the highest microturbine output power (59.01 watts) and pressure drop rate (9.71 meters H2O) were obtained when the inlet discharge was 42.61 m3/hr and the opening guide vane was 20 degrees. It also has the lowest output power (0.8 watts) and pressure drop rate (4.65 meters H2O) for a flow rate of 46 m3/hr without the guide vane. The coefficient of determination (R2) for the equations of microturbine output power and pressure drop was calculated to be 0.92 and 0.99, respectively.